CITRA PEREMPUAN BERHIJAB DALAM IKLAN SAMPO: SEBUAH KAJIAN PRAGMATIK - Nurjanah, Neneng; Pratiwi, Rifka A. (Universitas Negeri Surabaya, 2019)
This research explores the representation of hijab woman in the ads of Rejoice X Fatin: aku #Hijabisa. Employing relevance theory and qualitative research methods, this research focuses on (1) the speaker meaning which is presented in the ads of Rejoice X Fatin: Aku #Hijabisa (2) the representation of hijab woman in the ads of Rejoice X Fatin: Aku #Hijabisa. Findings in this research are: first the speaker?s meaning of utterance in this ad is hijab woman can take care of her body with this product and can do various activities without obstacle. Second, representations of young hijab woman are active, productive, and religious.